2009 2nd International Conference on Computer Science and Its Applications 2009
DOI: 10.1109/csa.2009.5404204
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Stepwise Forensic Approach to Incident Response and Computer Usage Analysis

Abstract: While traditional digital investigation is limited to cyber crimes, now it is an essential procedure on most of civil and criminal case. With the proliferation of the digital investigation in this situation, the need for the timely identification, analysis and interpretation of digital evidence is becoming more crucial. The general method of investigating the suspect's computer is laborious, time-consuming, complicated tasks and requires specialty on the part of forensic experts. In particular cases, such as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The new process model is opted to collect crucial evidence quickly and investigate the cases immediately. The Stepwise Forensic Process Model presents the stepwise and in-situ approach provides incident identification, recovery, analysis [12]. The SFPM suggest a new investigational model for selecting the target and analysing the relevant evidences only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The new process model is opted to collect crucial evidence quickly and investigate the cases immediately. The Stepwise Forensic Process Model presents the stepwise and in-situ approach provides incident identification, recovery, analysis [12]. The SFPM suggest a new investigational model for selecting the target and analysing the relevant evidences only.…”
Section: Resultsmentioning
confidence: 99%
“…The composition of Hbase database not only improves the data sharing rate, but also enhances ease for the analysts to perform digital forensic investigations. In [12] Kyung-Soo Lim, Seung Bong Lee and Sangjin Lee have emphasize that we need new process model to collect crucial evidence . The Stepwise Forensic Process Model provides stepwise and in-situ approach for providing incident description, recovery, analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lim et al identified that booting and uptime of a computer would be helpful to respond effectively to an information security incident [33]. Sbeyti used several kinds of information to observe user behavior on mobile devices, where power on/off is one such observation information [34].…”
Section: Usage Behaviorsmentioning
confidence: 99%
“…A Stepwise Forensic Approach to Incident Response and Computer Usage was proposed with the integration of two prior models; the Cyber Forensic Field Triage Process Model (CFFTPM) proposed by [7] and the Phased Investigation Methodology for Tracing Computer Usage (PIM) by [8]. CFFTPM formalises a real world investigative approach [9], affirming an onsite/field method that offers results within a short time frame without necessarily moving the suspecting/evidence media to a forensic lab for an exhaustive examination. The model emphasises a basis that; some incidences require swift and timely response, increased delay could imply greater harm to victims or assets, or better still the escape of a suspect.…”
Section: Stepwise Forensic Approachmentioning
confidence: 99%
“…The model emphasises a basis that; some incidences require swift and timely response, increased delay could imply greater harm to victims or assets, or better still the escape of a suspect. The PIM framework on the other hand centres on the selection of investigation targets, narrowing down the response and search to the barest minimum potential targets [9]. This allows for a prompt response to specific cases and affected systems.…”
Section: Stepwise Forensic Approachmentioning
confidence: 99%